Fashioned from nature - Ehrman, Edwina (V&A Publishing, 2018)
Fashion has always sought to celebrate nature - from sumptuous silks and floral patterns, to the spectacular creations of designers such as Alexander McQueen and Christian Dior, the two have long been entwined. Yet this reverence is sometimes combined with a damaging need for raw materials. From the seventeenth century to the present day, Fashioned from Nature examines our dependence on the natural world and the devastating effect of certain trends, as seen in the demand for ivory, fur, skins and exotic feathers. Today, intense consumerism and fast fashion have a different impact on the world around us, and this book discusses the need for a more responsible fashion cycle. But which has the greater environmental impact - a leather handbag or a white cotton t-shirt? Consider the effects of land clearance, insecticides and water consumption - not to mention washing after every wear - and the answer may not be completely clear. Fascinating and beautifully illustrated, this book will stimulate an important and timely debate
Published to accompany the exhibition "Fashioned from Nature" at the Victoria & Albert Museum, London from 21 April 2018 to 27 January 2019
New photography by Robert Auton, V&A Photographic Studio
Keywords: Geschichte 1600-; Textilien; Kleidung; Natur; Natur -- Motiv; Mode; Ökologie; Nachhaltigkeit; Ausstellungskatalog -- Victoria and Albert Museum -- 21.04.2018-27.01.2019 -- London; Bildband